Deconstructing Derrida - Peters, M. author. aut Link
VI, 224 p. 2 illus.
Keywords: Responding to Jacques Derrida's vision for what a 'new' humanities should strive toward, Peter Trifonas and Michael Peters gather together in a single volume original essays by major scholars in the humanities today. Using Derrida's seven programmatic theses as a springboard, the contributors aim to reimagine, as Derrida did, the tasks for the new humanities in such areas as history of literature, history of democracy, history of profession, idea of sovereignty, and history of man. Deconstructing Derrida engages Jacques Derrida's polemic on the future of the humanities to come and expands on the notion of what us proper to the humanities in the current age of globalism and change.